2018
DOI: 10.1111/all.13376
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes enhance neutrophil‐induced blister formation in an ex vivo model of bullous pemphigoid

Abstract: Our observations suggest that the interaction of cells, as shown here for monocytes and neutrophils, enhances mediator release resulting in an increased subepidermal blister formation. Thus, blocking intercellular cross talk promises a new therapeutic approach for blocking tissue damage in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Comparing the effect of two antibodies that deplete monocytes and neutrophils (anti-Ly6C/G) or only neutrophils (anti-Ly6G) suggests that the depletion of monocytes has an additional beneficial effect on experimental EBA ( 22 , 26 ). Moreover, monocytes are able to execute subepidermal cleft formation in an in vitro model of the disease ( 25 , 27 ). The roles of neutrophils and monocytes in pemphigoid diseases suggest that therapeutic principles targeting, like DMF, the recruitment of both neutrophils and monocytes into the skin may be superior to strategies solely targeting neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the effect of two antibodies that deplete monocytes and neutrophils (anti-Ly6C/G) or only neutrophils (anti-Ly6G) suggests that the depletion of monocytes has an additional beneficial effect on experimental EBA ( 22 , 26 ). Moreover, monocytes are able to execute subepidermal cleft formation in an in vitro model of the disease ( 25 , 27 ). The roles of neutrophils and monocytes in pemphigoid diseases suggest that therapeutic principles targeting, like DMF, the recruitment of both neutrophils and monocytes into the skin may be superior to strategies solely targeting neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In an ex vivo skin model, eosinophils stimulated with IL-5 in the presence of BP serum caused a dermal-epidermal splitting resembling BP. This splitting was significantly decreased upon adding DNase I, suggesting that EET formation plays at least a partial role 90 . These observations make eosinophils interesting targets for therapy 91 .…”
Section: Eets and Nets In Bullous Pemphigoidmentioning
confidence: 96%
“…Bullous pemphigoid (BP) is an autoimmune blistering skin disease characterized by an activation of autoreactive B and T cells, the production of pathogenetically relevant autoantibodies directed against the hemidesmosomal proteins BP180 and BP230, and a prominent eosinophil infiltration in the skin 90 . It has been shown that in prebullous lesions, a small subgroup of eosinophils have formed EETs consisting of mtDNA associated with eosinophil granular proteins 26 .…”
Section: Eets and Nets In Bullous Pemphigoidmentioning
confidence: 99%
“…121 Dimethyl fumarate Immune complex deposition at the dermal epidermal junction (DEJ) in pemphigoid underlies the subsequent complement activation, neutrophil extravasation and proteolytic destruction in experimental models of pemphigoid and EBA. 15,[125][126][127][128] Dimethyl fumarate (DMF) is a prodrug utilized in the treatment of autoimmune disorders psoriasis and multiple sclerosis. 129,130 Its therapeutic effect is realized through downregulation of the glycolytic enzyme glyceraldehyde 3-phosphate dehydrogenase and activation of nuclear factor erythroid 2-related factor 2 (NRF2) which stimulates expression of cytoprotective and antioxidant genes.…”
Section: Small Molecular Inhibitorsmentioning
confidence: 99%
“…Immune complex deposition at the dermal epidermal junction (DEJ) in pemphigoid underlies the subsequent complement activation, neutrophil extravasation and proteolytic destruction in experimental models of pemphigoid and EBA . Dimethyl fumarate (DMF) is a prodrug utilized in the treatment of autoimmune disorders psoriasis and multiple sclerosis .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%